2017
DOI: 10.2298/pan1702169j
|View full text |Cite
|
Sign up to set email alerts
|

Institutional quality and income inequality in the advanced countries

Abstract: The purpose of this paper is to shed more light on the effects of changes in quality of economic, legal and political institutions on income inequality in the advanced countries over the last two decades. Using the robust panel model on a sample of 21 OECD countries, it is found that the impact of elitization of society is more pronounced than the impact of unionization on income redistribution, but both effects are less expressed in comparison to the influence of institutional changes on redistribution. In a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 10 publications
2
25
0
1
Order By: Relevance
“…If the former is, over a very long run, consistently higher than the latter, then income inequality will increase. Institutions, welfare states, taxes and pro-labour policies, like those implemented between 1945 and 1975 in most advanced economies, contribute to reduce inequality or to maintain lower inequality (as also argued by Josifidis et al, 2017). Similarly, Alvaredo et al (2017) show that top income and wealth shares have increased in nearly all countries in recent decades.…”
Section: Global and National Inequalities In A Historical Perspectivementioning
confidence: 90%
“…If the former is, over a very long run, consistently higher than the latter, then income inequality will increase. Institutions, welfare states, taxes and pro-labour policies, like those implemented between 1945 and 1975 in most advanced economies, contribute to reduce inequality or to maintain lower inequality (as also argued by Josifidis et al, 2017). Similarly, Alvaredo et al (2017) show that top income and wealth shares have increased in nearly all countries in recent decades.…”
Section: Global and National Inequalities In A Historical Perspectivementioning
confidence: 90%
“…But there is controversy in literature about the factors explaining institutional quality of an economy. Josifidis et al (2017) empirically examined the impacts of changes in institutional quality on income inequalities in developed countries for the last two decades. It is argued that different interests of social groups are contributing to deteriorate income inequalities but their affects are not properly analyzed because distributional impacts of innovative disruptions are ignored.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, changes in the political structure, power of left-or right-wing parties and the election year, as well as institutions have important influence on public ex penditure policies (for instance, political and institutional determinants in OECD countries are explained in Miyazaki 2007, while Brady andLeicht, 2008, dealt with the power of par ties). Income inequality (United Nations, 2005;Josifidis et al, 2011;Josifidis, Supic, and Beker Pucar 2017), as well as impoverishment (Lelkes and Zolyomi, 2008) cause public policy interventions and therefore are important in explaining fiscal position across coun tries. Gibson, Palivos and Tavlas (2013) showed that fiscal balance variables were affected by global crisis differently in countries of European Union, due to absence of unique fiscal policy.…”
Section: Literature Reviewmentioning
confidence: 99%